Population genetics and external proficiency testing for HLA disease associations - Mrazek, Frantisek (Frontiers in Genetics, 2023)
Numerous associations of HLA variants with susceptibility to diseases, namely those with an immunopathological component, have been described to date. The strongest HLA associations were incorporated into the standard algorithms for the diagnostics. Disease-associated HLA variants are routinely detected by various techniques including DNA-based assays. For the identification of HLA markers or their combinations with the highest diagnostic value and those with frequent clinical indications (e.g. HLA-B*27, -B*57:01, -DQ2/-DQ8, -DQB1*06:02), diagnostic tests that focus on a single or limited number of specific HLA antigens/alleles, have already been developed; the use of complete typing for particular HLA loci is a relevant alternative. Importantly, external proficiency testing (EPT) became an integral part of good laboratory practice for HLA disease associations in accredited laboratories and not only supports correct “technical” identification of the associated HLA variants, but also adequate interpretation of the results to the clinicians. In the present article selected aspects of EPT for HLA disease associations related to population genetics are reviewed and discussed with the emphasis on the optimal level of HLA typing resolution, population-based differences in disease associated HLA alleles within the allelic group, distribution and linkage disequilibrium of HLA alleles in particular populations and interpretation of the presence of less common HLA variants/haplotypes. In conclusion, the laboratories that perform and interpret the tests to the clinicians, producers of the certified diagnostics and EPT providers should consider, among others, the genetic characteristics of the populations in order to optimise the diagnostic value of the tests for disease-associated HLA variants.